2000
DOI: 10.1017/s1355838200001540
|View full text |Cite
|
Sign up to set email alerts
|

The final step in the formation of 25S rRNA in Saccharomyces cerevisiae is performed by 5′ → 3′ exonucleases

Abstract: The final stage in the formation of the two large subunit rRNA species in Saccharomyces cerevisiae is the removal of internal transcribed spacer 2 (ITS2) from the 27SB precursors. This removal is initiated by endonucleolytic cleavage approximately midway in ITS2. The resulting 7S pre-rRNA, which is easily detectable, is then converted into 5.8S rRNA by the concerted action of a number of 3'-->5' exonucleases, many of which are part of the exosome. So far the complementary precursor to 25S rRNA resulting from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 35 publications
5
108
1
1
Order By: Relevance
“…The distribution of Rpl25p-eGFP was followed during depletion of Nop7p (Fig+ 3B)+ During growth of the GAL::nop7 strain on RSG medium, Rpl25-eGFP showed the normal, predominantly cytoplasmic distribution+ After transfer to glucose medium for 2 h, increased nuclear staining of Rpl25-eGFP was already visible, and accumulation was strong after 8 h+ The distribution of Rpl25-eGFP fluorescence matched that of DAPI staining, indicating that it was not restricted to the nucleolus+ We conclude that Nop7p is required to allow the export of precursors to the 60S ribosomal subunit from the nucleoplasm to the cytoplasm+ 5+8S S is processed from the 27SB S pre-rRNA, whereas 5+8S L is processed from 27SB L (see Fig+ 1B)+ To determine the levels of the 27SB species, they were analyzed by primer extension (Fig+ 5A) using an oligo hybridizing within the 39 region of ITS2 (oligo 006; see Fig+ 1A)+ Following growth of the GAL::nop7 strain on glucose medium, the level of 27SB S was clearly reduced relative to 27SB L , as shown by the primer extension stops at B 1S and B 1L , respectively (Fig+ 5A, lane 4)+ Consistent with the northern analysis, little alteration was seen in the level of 27SA 2 , as shown by the primer extension stop at site A 2 + In contrast, the level of 27SA 3 , shown by the stop at site A 3 , was substantially elevated+ Using a primer hybridizing within the mature 25S rRNA (oligo 007; see Fig+ 1A), slight accumulation was seen for the primer extension stop at site C 2 , the 59 end of the 26S pre-rRNA (Fig+ 5B)+ This effect was weak, however, and its significance is unclear+ Pulse-chase analysis with [H 3 ]-uracil was performed 16 h after transfer to glucose minimal medium (Fig+ 6)+ Comparison of the wild-type and GAL::nop7 strains showed that accumulation of the 5+8S rRNA was mildly delayed+ Together these data show that depletion of Nop7p resulted in reduced exonuclease digestion from site A 3 to site B 1S + In consequence, the level of the 27SA 3 pre-rRNA was substantially increased, whereas the 27SB S pre-rRNA was depleted together with the 7S S and 6S S pre-rRNAs, leading to reduced accumulation of the mature 5+8S S rRNA+ The 59 end of the 25S rRNA is also generated by exonuclease digestion (Geerlings et al+, 2000;see Fig+ 1B), but this did not appear to be strongly affected, as only a small increase was seen in the primer extension stop at site C 2 + The mild effects on 35S processing are likely to be indirect, as many mutations that inhibit synthesis of 60S subunits result in partial inhibition of the early pre-rRNA processing steps (for further discussion see Venema & Tollervey, 1999)+…”
Section: Yeast Nop7p Is Required For 60s Subunit Export and Interactsmentioning
confidence: 92%
“…The distribution of Rpl25p-eGFP was followed during depletion of Nop7p (Fig+ 3B)+ During growth of the GAL::nop7 strain on RSG medium, Rpl25-eGFP showed the normal, predominantly cytoplasmic distribution+ After transfer to glucose medium for 2 h, increased nuclear staining of Rpl25-eGFP was already visible, and accumulation was strong after 8 h+ The distribution of Rpl25-eGFP fluorescence matched that of DAPI staining, indicating that it was not restricted to the nucleolus+ We conclude that Nop7p is required to allow the export of precursors to the 60S ribosomal subunit from the nucleoplasm to the cytoplasm+ 5+8S S is processed from the 27SB S pre-rRNA, whereas 5+8S L is processed from 27SB L (see Fig+ 1B)+ To determine the levels of the 27SB species, they were analyzed by primer extension (Fig+ 5A) using an oligo hybridizing within the 39 region of ITS2 (oligo 006; see Fig+ 1A)+ Following growth of the GAL::nop7 strain on glucose medium, the level of 27SB S was clearly reduced relative to 27SB L , as shown by the primer extension stops at B 1S and B 1L , respectively (Fig+ 5A, lane 4)+ Consistent with the northern analysis, little alteration was seen in the level of 27SA 2 , as shown by the primer extension stop at site A 2 + In contrast, the level of 27SA 3 , shown by the stop at site A 3 , was substantially elevated+ Using a primer hybridizing within the mature 25S rRNA (oligo 007; see Fig+ 1A), slight accumulation was seen for the primer extension stop at site C 2 , the 59 end of the 26S pre-rRNA (Fig+ 5B)+ This effect was weak, however, and its significance is unclear+ Pulse-chase analysis with [H 3 ]-uracil was performed 16 h after transfer to glucose minimal medium (Fig+ 6)+ Comparison of the wild-type and GAL::nop7 strains showed that accumulation of the 5+8S rRNA was mildly delayed+ Together these data show that depletion of Nop7p resulted in reduced exonuclease digestion from site A 3 to site B 1S + In consequence, the level of the 27SA 3 pre-rRNA was substantially increased, whereas the 27SB S pre-rRNA was depleted together with the 7S S and 6S S pre-rRNAs, leading to reduced accumulation of the mature 5+8S S rRNA+ The 59 end of the 25S rRNA is also generated by exonuclease digestion (Geerlings et al+, 2000;see Fig+ 1B), but this did not appear to be strongly affected, as only a small increase was seen in the primer extension stop at site C 2 + The mild effects on 35S processing are likely to be indirect, as many mutations that inhibit synthesis of 60S subunits result in partial inhibition of the early pre-rRNA processing steps (for further discussion see Venema & Tollervey, 1999)+…”
Section: Yeast Nop7p Is Required For 60s Subunit Export and Interactsmentioning
confidence: 92%
“…The 27SB S and 27SB L pre-rRNAs undergo identical processing by endonucleolytic cleavage at the C 2 site in ITS2 to generate the 25.5S and 7S S or 7S L pre-rRNAs. The 59 end of 25.5S prerRNA is trimmed by Rat1 to form mature 25S rRNA (Geerlings et al 2000). The 39 ends of 7S pre-rRNAs are processed in several steps to produce mature 5.8S S and 5.8S L rRNAs differing by 6 nt at their 59 ends Mitchell et al 1996).…”
Section: Processing Modification and Folding Of Pre-rrnamentioning
confidence: 99%
“…The 59-39 exonucleases Rat1 and Rrp17 rapidly process 25.5S pre-rRNA to 25S rRNA (Geerlings et al 2000). Trimming of 7S pre-rRNA to 5.8S S or 5.8S L rRNAs requires at least four steps and a number of different nucleases and occurs sequentially in the nucleus and then the cytoplasm (Henry et al1994;Tollervey 2005, 2010).…”
Section: Construction Of Stable Early Assembly Intermediatesmentioning
confidence: 99%
“…It is required after cleavage and polyadenylation of nascent transcripts to degrade the downstream cleaved RNA from 5'-3' direction (Richard and Manley, 2009). Rat1p is also involved in the process of rRNA maturation: ITS1, one of the internal transcribed spacers (ITS1 and ITS2), locates at the flanking site of 5.8S rRNA, which is trimmed by Rat1p from the 5' end of the rRNA precursor after endoribonuclease cleavage (Henry et al, 1994;Geerlings et al, 2000). Rat1p recently has been suggested to play an important role in telomere maintenance by degrading telomeric repeat-containing RNA (TERRA), which is a long non-coding RNA that represses telomerase activity, and thus activates telomere elongation (Luke et al, 2008).…”
Section: Rat1p/xrn2mentioning
confidence: 99%